Silicon nitride ceramic and preparation method thereof

Through the combination of modified aluminum oxide, aluminum nitride, magnesium fluoride and other materials and the nitriding sintering process, the silicon aluminum nitride magnesium phase is formed, which solves the problems of low thermal conductivity and reduced mechanical properties of silicon nitride ceramics, and the combination of high thermal conductivity and good mechanical properties is achieved.

CN118894728BActive Publication Date: 2025-03-11HUNAN XIANGCI TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410923369.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-10
Publication Date
2025-03-11
Estimated Expiration
2044-07-10

AI Technical Summary

Technical Problem

The existing silicon nitride ceramics have low thermal conductivity, and long-term heating treatment at high temperatures leads to abnormal growth of grains, reduced mechanical properties, and high production costs.

Method used

The combination of modified alumina, aluminum nitride, magnesium fluoride, silicon nitride powder, sintering agent and toughening agent is adopted to form the silicon alumina nitride magnesium phase through the nitride sintering process to reduce the oxygen content and prevent the formation of lattice oxygen, thereby improving the thermal conductivity, improving the performance of the grain boundary phase and enhancing the strength and toughness of the material.

Benefits of technology

It effectively improves the thermal conductivity of silicon nitride ceramics, improves mechanical properties, reduces production costs, and enhances the toughness of the material.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present application discloses a silicon nitride ceramic and a preparation method thereof, which relates to the technical field of ceramic preparation; the ceramic includes the following preparation raw materials: modified alumina, magnesium fluoride, silicon nitride powder, a sintering aid and a toughening agent; the sintering aid is yttrium oxide; the toughening agent is silicon carbide; the modified alumina includes the following preparation raw materials: alumina, ammonia water, a coupling agent, polyethylene glycol, a phenolic resin and a nitrogen source. Among them, during the sintering process, the nitrogen source, alumina and carbon source in the modified alumina react and transform into aluminum nitride, and aluminum nitride and silicon nitride form a silicon nitride aluminum phase during the sintering process, and the addition of magnesium fluoride will also diffuse the magnesium element to the surface of the silicon nitride aluminum, forming silicon aluminum magnesium nitride in situ, thereby effectively reducing the oxygen content in the sintered phase and hindering the formation of lattice oxygen, thereby further improving the thermal conductivity of the silicon nitride ceramic.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of ceramic preparation, and in particular to a silicon nitride ceramic and a preparation method thereof. Background Art

[0002] As a structural ceramic, silicon nitride ceramics have excellent mechanical properties such as high strength, high fracture toughness, and good thermal shock resistance. As a strong covalent bond compound, silicon nitride is usually sintered by adding metal oxides. During the sintering process, these oxides form an M-Si-ON eutectic liquid phase with SiO2 on the surface of silicon nitride powder and a small amount of silicon nitride at high temperature, and dense ceramics are obtained by liquid phase sintering: However, the thermal conductivity of the obtained silicon nitride ceramics is low.

[0003] In the related art, the material with the highest thermal conductivity is obtained by hot pressing and sintering at 1800℃ and then hot isostatic pressing at 2500℃ for 2 hours in the direction parallel to the β-Si3N4 seed crystal. However, the high temperature and long time heating treatment causes abnormal growth of ceramic grains, a sharp decrease in mechanical properties, and high production costs. Summary of the invention

[0004] The present application has been made in view of the above-mentioned problems, and an object of the present application is to provide a silicon nitride ceramic having high thermal conductivity.

[0005] In a first aspect, the present application provides a silicon nitride ceramic, comprising the following raw materials in parts by weight:

[0006] 100 parts of silicon nitride powder, 10 to 20 parts of modified alumina, 5 to 10 parts of aluminum nitride, 10 to 20 parts of magnesium fluoride, 5 to 10 parts of sintering aid and 5 to 10 parts of toughening agent;

[0007] The modified alumina comprises the following preparation raw materials:

[0008] 100 parts of aluminum oxide, 30 to 40 parts of alkali, 2 to 3 parts of coupling agent, 1 to 2 parts of polyethylene glycol, 40 to 50 parts of phenolic resin and 200 to 300 parts of nitrogen source;

[0009] The phenolic resin comprises the following preparation raw materials:

[0010] 100 parts of phenolic compound, 100 parts to 150 parts of formaldehyde, 2 parts to 3 parts of amine catalyst, 6 parts to 20 parts of boric acid, 50 parts to 60 parts of melamine, and 0 parts to 15 parts of solvent;

[0011] The phenolic compound includes phenol or 3-hydroxyphenylboronic acid.

[0012] According to one of the technical solutions of the present application, there are at least the following beneficial effects:

[0013] The raw materials for preparing silicon nitride ceramics in this application are composed of modified alumina, aluminum nitride, magnesium fluoride, silicon nitride powder, sintering aids and toughening agents; wherein the nitrogen source and carbon source (mainly formed by phenolic resin) in the modified alumina promote the conversion of alumina into aluminum nitride during the sintering process, and aluminum nitride and silicon nitride form silicon nitride aluminum phase during the sintering process, and the addition of magnesium fluoride will also diffuse magnesium powder to the surface of silicon nitride aluminum, forming silicon nitride aluminum magnesium in situ, thereby effectively reducing the oxygen content in the sintered phase, hindering the formation of lattice oxygen, and further improving the thermal conductivity of silicon nitride ceramics. Fluoride ions can also form volatile silicon fluoride with silicon ions in the system, thereby breaking the crystal medium of the system and promoting the fusion of the system.

[0014] At the same time, alumina can also play a partial role in aiding sintering. Working together with the sintering aid, it is beneficial to reduce the sintering temperature and improve the performance of the grain boundary phase, thereby increasing the strength of the material.

[0015] The addition of toughening agent is beneficial to enhance the toughness of silicon nitride ceramics.

[0016] The raw materials for preparing modified alumina in the present application include: alumina, alkali, coupling agent, polyethylene glycol, phenolic resin and nitrogen source; the present application uses coupling agent and polyethylene glycol to modify and disperse alumina, so that the alumina is dispersed, the compatibility of alumina and phenolic resin is increased, and the aluminum source, carbon source (phenolic resin) and nitrogen source can be evenly mixed; the nitrogen source reacts in situ with the evenly mixed aluminum source and carbon source, thereby reducing the synthesis temperature of silicon aluminum nitride, and finally obtaining a ceramic material with excellent performance.

[0017] The use of a larger amount of nitrogen source and phenolic resin is to allow the aluminum oxide to react fully without any residue.

[0018] In the present application, the raw materials for preparing the phenolic resin contain 3-hydroxyphenylboric acid, boric acid and melamine, thereby introducing more boron and nitrogen elements into the phenolic resin, and the boron and nitrogen elements can form boron nitride, which is beneficial to further improve the thermal conductivity and mechanical strength of the material; at the same time, melamine can also reduce the crosslinking degree of the phenolic resin, making it easy to crack at high temperatures. At the same time, due to the introduction of other groups in the crosslinked structure, the regularity of the carbon material is destroyed, so the groups are more likely to break during the cracking process. The residual carbon produced by the high-temperature pyrolysis of the phenolic resin undergoes a carbon thermal reduction reaction with the oxide film formed on the surface of the silicon nitride, effectively reducing the oxygen content after sintering and improving the nitridation rate.

[0019] According to some embodiments of the present application, the amine catalyst is ethylenediamine.

[0020] According to some embodiments of the present application, the solvent is at least one of water, ethanol, methanol, acetone, tetrahydrofuran, methane and chloroform.

[0021] According to some embodiments of the present application, the particle size of the aluminum oxide is 10 nm to 1000 nm.

[0022] According to some embodiments of the present application, the coupling agent is γ-piperazinepropylmethyldimethoxysilane.

[0023] According to some embodiments of the present application, the Mw (weight average molecular weight) of the polyethylene glycol is 800-2000.

[0024] According to some embodiments of the present application, the Mw of the polyethylene glycol is 950-1050.

[0025] According to some embodiments of the present application, the base is aqueous ammonia.

[0026] According to some embodiments of the present application, the nitrogen source is melamine.

[0027] Melamine is used as a nitrogen source, and highly active ammonia is produced by decomposition of the nitrogen source during the heating and insulation process.

[0028] According to some embodiments of the present application, the sintering aid is yttrium oxide.

[0029] Yttrium oxide plays a certain role in the crystallization of grain boundary phase and the improvement of material strength.

[0030] According to some embodiments of the present application, the toughening agent is silicon carbide.

[0031] According to some embodiments of the present application, the silicon nitride particle size is 1 μm to 3 μm.

[0032] According to some embodiments of the present application, the yttrium oxide particle size is 1 μm to 10 μm.

[0033] The second aspect of the present application discloses a method for preparing the above silicon nitride ceramic, comprising the following steps:

[0034] The modified alumina, aluminum nitride, magnesium fluoride, silicon nitride powder, a sintering aid and a toughening agent are mixed and pressed to obtain a pressed product;

[0035] The pressed product is nitrided and sintered to obtain silicon nitride ceramics;

[0036] The atmosphere of the nitriding sintering is nitrogen;

[0037] The temperature of the nitriding sintering is 700°C to 1700°C.

[0038] According to some embodiments of the present application, the pressing pressure is 5 MPa to 10 MPa.

[0039] According to some embodiments of the present application, the pressing time is 5 min to 10 min.

[0040] According to some embodiments of the present application, the nitriding sintering includes a first stage nitriding, a second stage nitriding and a third stage nitriding.

[0041] According to some embodiments of the present application, the temperature of the first stage nitridation is 700°C to 800°C.

[0042] According to some embodiments of the present application, the pressure of nitrogen in the first nitridation process is 0.8 MPa to 1 MPa.

[0043] According to some embodiments of the present application, the nitriding time in the first nitriding process is 1 hour to 6 hours.

[0044] According to some embodiments of the present application, the temperature of the second stage nitridation is 1500°C to 1700°C.

[0045] According to some embodiments of the present application, the pressure of nitrogen in the second nitridation process is 4 MPa to 6 MPa.

[0046] According to some embodiments of the present application, the nitriding time in the second nitriding process is 1 hour to 6 hours.

[0047] According to some embodiments of the present application, the temperature of the third stage nitridation is 950°C to 1000°C.

[0048] According to some embodiments of the present application, the pressure of nitrogen in the third nitridation process is 8 MPa to 10 MPa.

[0049] According to some embodiments of the present application, the nitridation time in the third nitridation process is 1 hour to 6 hours.

[0050] In the present application, the nitrogen source forms nitrides with elements such as aluminum and silicon during the sintering process; the low nitrogen pressure in the initial sintering stage can reduce the N content in the liquid phase, reduce the viscosity of the liquid phase, and facilitate the precipitation of nitrides from the liquid phase. In the later high and medium temperature sintering stage, high-density nitride ceramics are obtained under high temperature and high nitrogen pressure.

[0051] The present application uses step-by-step pre-sintering to form a preliminary crystalline structure between the various mixed material components, providing a structural basis for subsequent sintering; secondly, the various prepared raw materials are used in combination and sintered to form a composite ceramic material, thereby obtaining a ceramic material with excellent performance.

[0052] According to some embodiments of the present application, the method for preparing the modified alumina comprises the following steps:

[0053] Mixing alumina, a base, a coupling agent, polyethylene glycol and ethanol to prepare a first mixture;

[0054] The nitrogen source, the phenolic resin and the first mixture are mixed and then dried to prepare modified alumina.

[0055] According to some embodiments of the present application, the drying temperature is 80°C to 90°C. DETAILED DESCRIPTION

[0056] In order to make the purpose, technical solutions and advantages of the present application clearer, the present application is described and illustrated below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not intended to limit the present application. Based on the embodiments provided in the present application, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present application.

[0057] Obviously, the following descriptions are only some examples or embodiments of the present application. For ordinary technicians in this field, the present application can also be applied to other similar scenarios without creative work. In addition, it can also be understood that although the efforts made in this development process may be complicated and lengthy, for ordinary technicians in the field related to the content disclosed in this application, some changes in design, manufacturing or production based on the technical content disclosed in this application are just conventional technical means, and should not be understood as insufficient content disclosed in this application.

[0058] However, unnecessary detailed descriptions may be omitted. For example, detailed descriptions of well-known matters and repeated descriptions of substantially the same structures may be omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate understanding by those skilled in the art. In addition, the following description is provided for those skilled in the art to fully understand the present application and is not intended to limit the subject matter described in the claims.

[0059] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0060] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0061] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values ​​or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.

[0062] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.

[0063] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.

[0064] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.

[0065] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.

[0066] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).

[0067] The following will be clearly and completely described in conjunction with the technical solutions in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0068] The manufacturers and performance parameters of some raw materials in this application are as follows:

[0069] Alumina: McLean, product number A766523, particle size 60nm; product number: A871959, particle size 300-400 mesh;

[0070] Aluminum nitride: McLean, product number A835827, particle size 0.5 μm.

[0071] Silicon nitride powder: McLean, product number S817703 (β phase), particle size 1 μm to 3 μm.

[0072] Yttrium oxide: McLean, product number Y835830, particle size 1 μm.

[0073] Silicon carbide: McLean, product number S799162, particle size 600nm~800nm.

[0074] Polyethylene glycol: PEG-1000 (Mw is 950-1050).

[0075] Example 1

[0076] This embodiment is a silicon nitride ceramic, which is composed of the following raw materials in parts by weight:

[0077] 100 parts of silicon nitride powder, 18 parts of modified alumina, 8 parts of aluminum nitride, 18 parts of magnesium fluoride, 10 parts of sintering aid (yttrium oxide) and 10 parts of toughening agent (silicon carbide);

[0078] The modified alumina in this embodiment includes the following preparation raw materials:

[0079] 100 parts of aluminum oxide (particle size 60 nm), 40 parts of alkali (ammonia water, mass fraction 25%), 3 parts of coupling agent (γ-piperazinepropylmethyldimethoxysilane, CAS No.: 128996-12-3), 2 parts of polyethylene glycol, 45 parts of phenolic resin and 300 parts of nitrogen source (melamine);

[0080] The preparation method of modified alumina in this embodiment consists of the following steps:

[0081] S1. Adding aluminum oxide to ethanol (the mass volume ratio of aluminum oxide to ethanol is 1 g:10 mL), and stirring until a first mixture is formed;

[0082] Adding a base, a coupling agent and polyethylene glycol to the first mixture in sequence, stirring for 2 h (600 rpm), to obtain a second mixture;

[0083] S2, adding phenolic resin to ethanol (the mass volume ratio of phenolic resin to ethanol is 1 g:10 mL) to prepare a third mixture;

[0084] The second mixture, the third mixture and the nitrogen source were mixed and stirred for 0.5 h (600 rpm) to obtain a fourth mixture. The fourth mixture was dried at 80° C. and the solid phase was collected to obtain modified alumina.

[0085] In this embodiment, the phenolic resin includes the following preparation raw materials:

[0086] 100 parts of 3-hydroxyphenylboric acid, 150 parts of formaldehyde, 3 parts of amine catalyst (ethylenediamine), 10 parts of boric acid, 60 parts of melamine, and 15 parts of solvent (the mass ratio of water to ethanol is 13:2).

[0087] The preparation method of phenolic resin in this embodiment consists of the following steps:

[0088] 3-Hydroxyphenylboric acid, formaldehyde, an amine catalyst, boric acid, melamine and a solvent are mixed, reacted at 130° C. for 24 hours, and a solid phase is collected. The obtained solid phase is separated, washed and dried to obtain a phenolic resin.

[0089] The preparation method of silicon nitride ceramic in this embodiment consists of the following steps:

[0090] The modified alumina, aluminum nitride, magnesium fluoride, silicon nitride powder, a sintering aid and a toughening agent are mixed and pressed (pressing pressure is 10 MPa, time is 8 min) to obtain a pressed product;

[0091] The pressed product is nitrided and sintered to obtain silicon nitride ceramics;

[0092] Nitriding sintering consists of the first heating, the first stage nitriding, the second heating, the second stage nitriding, the first cooling and the third stage nitriding;

[0093] The heating rate of the first heating is 30℃ / min;

[0094] The temperature of the first stage of nitriding is 750°C;

[0095] The pressure of nitrogen in the first stage of nitriding is 0.9MPa;

[0096] The nitriding time in the first nitriding process is 3h;

[0097] The heating rate of the second heating is 20℃ / min;

[0098] The temperature of the second stage nitriding is 1600°C;

[0099] The pressure of nitrogen in the second nitriding process is 6MPa;

[0100] The nitriding time in the second nitriding process is 6h;

[0101] During the process from the second stage to the third stage, the temperature is first lowered to 980°C, and then the third stage is carried out at a constant temperature;

[0102] The temperature of the third stage nitriding is 980°C;

[0103] The pressure of nitrogen in the third nitriding process is 10MPa;

[0104] The nitriding time in the third nitriding process is 4 hours.

[0105] Example 2

[0106] This embodiment is a silicon nitride ceramic. The difference between this embodiment and embodiment 1 is that the silicon nitride ceramic is composed of the following raw materials in parts by weight:

[0107] 100 parts of silicon nitride powder, 10 parts of modified alumina, 10 parts of aluminum nitride, 20 parts of magnesium fluoride, 10 parts of sintering aid (yttrium oxide) and 10 parts of toughening agent (silicon carbide);

[0108] The modified alumina in this embodiment includes the following preparation raw materials:

[0109] 100 parts of aluminum oxide (particle size 60 nm), 40 parts of alkali (ammonia water, mass fraction 25%), 3 parts of coupling agent (γ-piperazinepropylmethyldimethoxysilane, CAS No.: 128996-12-3), 2 parts of polyethylene glycol, 40 parts of phenolic resin (same as Example 1) and 200 parts of nitrogen source (melamine);

[0110] The preparation method of modified alumina in this example is carried out by referring to Example 1.

[0111] The preparation method of silicon nitride ceramic in this embodiment is carried out with reference to Example 1.

[0112] Example 3

[0113] This embodiment is a silicon nitride ceramic, which is composed of the following raw materials in parts by weight:

[0114] 100 parts of silicon nitride powder, 20 parts of modified alumina, 5 parts of aluminum nitride, 10 parts of magnesium fluoride, 10 parts of sintering aid (yttrium oxide) and 10 parts of toughening agent (silicon carbide);

[0115] The modified alumina in this embodiment includes the following preparation raw materials:

[0116] 100 parts of aluminum oxide (particle size 60 nm), 40 parts of alkali (ammonia water, mass fraction 25%), 3 parts of coupling agent (γ-piperazinepropylmethyldimethoxysilane, CAS No.: 128996-12-3), 2 parts of polyethylene glycol, 50 parts of phenolic resin and 300 parts of nitrogen source (melamine);

[0117] The preparation method of modified alumina in this example is carried out by referring to Example 1.

[0118] In this embodiment, the phenolic resin includes the following preparation raw materials:

[0119] 100 parts of 3-hydroxyphenylboric acid, 150 parts of formaldehyde, 3 parts of amine catalyst (ethylenediamine), 20 parts of boric acid, 50 parts of melamine, and 15 parts of solvent (the mass ratio of water to ethanol is 13:2).

[0120] The preparation method of the phenolic resin in this example is carried out with reference to Example 1.

[0121] The preparation method of silicon nitride ceramic in this embodiment is carried out with reference to Example 1.

[0122] Example 4

[0123] This embodiment is a silicon nitride ceramic, which differs from Embodiment 1 in that:

[0124] The method for preparing silicon nitride ceramics in this embodiment comprises the following steps:

[0125] The modified alumina, aluminum nitride, magnesium fluoride, silicon nitride powder, a sintering aid and a toughening agent are mixed and pressed (pressing pressure is 10 MPa, time is 8 min) to obtain a pressed product;

[0126] The pressed product is nitrided and sintered to obtain silicon nitride ceramics;

[0127] Nitriding sintering consists of heating and nitriding;

[0128] The heating rate of the heating is 30°C / min;

[0129] The nitriding temperature is 1600°C;

[0130] The pressure of nitrogen is 6MPa;

[0131] The nitriding time during the nitriding process is 13 hours.

[0132] Example 5

[0133] This embodiment is a silicon nitride ceramic, and the difference from the embodiment 1 is only that:

[0134] The particle size of alumina is 300-400 mesh.

[0135] Example 6

[0136] This embodiment is a silicon nitride ceramic, which is composed of the following raw materials in parts by weight:

[0137] 100 parts of silicon nitride powder, 10 parts of modified alumina, 8 parts of aluminum nitride, 18 parts of magnesium fluoride, 10 parts of sintering aid (yttrium oxide) and 10 parts of toughening agent (silicon carbide);

[0138] The modified alumina in this embodiment includes the following preparation raw materials:

[0139] 100 parts of aluminum oxide, 40 parts of alkali (ammonia water, mass fraction is 25%), 3 parts of coupling agent (γ-piperazinepropylmethyldimethoxysilane, CAS No.: 128996-12-3), 2 parts of polyethylene glycol, 45 parts of phenolic resin and 300 parts of nitrogen source (melamine);

[0140] The preparation method of modified alumina in this example is carried out with reference to Example 5.

[0141] In this embodiment, the phenolic resin includes the following preparation raw materials:

[0142] 100 parts of phenol, 150 parts of formaldehyde, 3 parts of amine catalyst (ethylenediamine), 10 parts of boric acid, 60 parts of melamine, and 15 parts of solvent (the mass ratio of water to ethanol is 13:2).

[0143] The preparation method of phenolic resin in this embodiment consists of the following steps:

[0144] Phenol, formaldehyde, an amine catalyst, boric acid, melamine and a solvent are mixed and reacted at 130° C. for 24 hours. The solid phase is collected and the obtained solid phase is separated, washed and dried to obtain a phenolic resin.

[0145] The preparation method of silicon nitride ceramic in this embodiment is carried out with reference to that in Embodiment 5.

[0146] Comparative Example 1

[0147] This comparative example is a silicon nitride ceramic, which is different from Example 5 in that the silicon nitride ceramic is composed of the following raw materials in parts by weight:

[0148] 100 parts of silicon nitride powder, 10 parts of modified alumina, 10 parts of sintering aid (yttrium oxide) and 10 parts of toughening agent (silicon carbide);

[0149] The modified alumina in this comparative example is the modified alumina in Example 5.

[0150] The preparation method of silicon nitride ceramic in this comparative example consists of the following steps:

[0151] Aluminum nitride powder, modified alumina, sintering aid and toughening agent are mixed and pressed (pressing pressure is 10 MPa, time is 8 min) to obtain a pressed product;

[0152] The pressed product is nitrided and sintered to obtain silicon nitride ceramics.

[0153] The nitriding sintering parameters are carried out according to Example 5.

[0154] Comparative Example 2

[0155] This comparative example is a silicon nitride ceramic, which is different from Example 5 in that the silicon nitride ceramic is composed of the following raw materials in parts by weight:

[0156] 100 parts of silicon nitride powder, 10 parts of modified alumina, 8 parts of aluminum nitride, 10 parts of sintering aid (yttrium oxide) and 10 parts of toughening agent (silicon carbide);

[0157] The modified alumina in this comparative example is the modified alumina in Example 5.

[0158] The preparation method of silicon nitride ceramic in this comparative example consists of the following steps:

[0159] Silicon nitride powder, modified alumina, aluminum nitride, a sintering aid and a toughening agent are mixed and pressed (pressing pressure is 10 MPa, time is 8 min) to obtain a pressed product;

[0160] The pressed product is nitrided and sintered to obtain silicon nitride ceramics.

[0161] The nitriding sintering parameters are carried out according to Example 5.

[0162] Comparative Example 3

[0163] This comparative example is a silicon nitride ceramic, which is composed of the following raw materials in parts by weight:

[0164] 100 parts of silicon nitride powder, 10 parts of aluminum oxide (particle size is 300-400 mesh), 8 parts of aluminum nitride, 18 parts of magnesium fluoride, 10 parts of sintering aid (yttrium oxide) and 10 parts of toughening agent (silicon carbide);

[0165] The preparation method of silicon nitride ceramic in this comparative example consists of the following steps:

[0166] Silicon nitride powder, aluminum oxide, aluminum nitride, magnesium fluoride, a sintering aid and a toughening agent are mixed and pressed (pressing pressure is 10 MPa, time is 8 min) to obtain a pressed product;

[0167] The pressed product is nitrided and sintered to obtain silicon nitride ceramics.

[0168] The nitriding sintering parameters are carried out according to Example 5.

[0169] Comparative Example 4

[0170] This comparative example is a silicon nitride ceramic, which is composed of the following raw materials in parts by weight:

[0171] 100 parts of silicon nitride powder, 10 parts of modified alumina, 8 parts of aluminum nitride, 18 parts of magnesium fluoride, 10 parts of sintering aid (yttrium oxide) and 10 parts of toughening agent (silicon carbide);

[0172] The modified alumina in this comparative example includes the following preparation raw materials:

[0173] 100 parts of alumina (particle size 300-400 mesh), 40 parts of alkali (ammonia water, mass fraction 25%), 3 parts of coupling agent (γ-piperazinepropylmethyldimethoxysilane, CAS No.: 128996-12-3), 2 parts of polyethylene glycol;

[0174] The preparation method of modified alumina in this comparative example consists of the following steps:

[0175] Adding aluminum oxide to ethanol (the mass volume ratio of aluminum oxide to ethanol is 1 g:10 mL), and stirring until a first mixture is formed;

[0176] Adding a base, a coupling agent and polyethylene glycol to the first mixture in sequence, stirring for 2 h (600 rpm), to obtain a second mixture;

[0177] The second mixture was dried at 80° C., and the solid phase was collected to obtain modified alumina.

[0178] The preparation method of silicon nitride ceramic in this comparative example is carried out with reference to Example 5.

[0179] The performance test results of the embodiments and comparative examples of the present application are shown in Table 1.

[0180] Table 1

[0181] - Thermal conductivity (W / m·K) Flexural strength(MPa) Example 1 180.9 1072 Example 2 168.1 1029 Example 3 177.6 1057 Example 4 162.6 1098 Example 5 156.3 1007 Example 6 145.3 982 Comparative Example 1 108.9 812 Comparative Example 2 96.6 837 Comparative Example 3 73.7 728 Comparative Example 4 91.8 783

[0182] The difference between Example 4 and Example 1 is that the sintering methods are different. No pre-sintering is performed in Example 4, which affects the formation of the preliminary crystalline structure, thereby affecting the performance of the final alumina ceramic, resulting in poor thermal conductivity and mechanical properties.

[0183] The difference between Example 5 and Example 1 is that the alumina particle size in Example 5 is larger and more difficult to disperse. In the process of preparing modified alumina, the compatibility of alumina with phenolic resin and the like is relatively poor, and the reaction effect with carbon source and nitrogen source during sintering is relatively poor, which affects the performance of the final alumina ceramic and results in poor thermal conductivity and mechanical properties.

[0184] The difference between Example 5 and Example 6 is that 3-hydroxyphenylboric acid is not introduced in Example 6, and the content of boron nitride is reduced, which affects the performance of the final alumina ceramic, resulting in poor thermal conductivity and mechanical properties.

[0185] The difference between Example 5 and Comparative Example 1 is that: in Comparative Example 1, magnesium fluoride and aluminum nitride powder are not added, and magnesium aluminum silicon nitride is not formed, which affects the performance of the final alumina ceramic, resulting in poor thermal conductivity and mechanical properties.

[0186] The difference between Example 5 and Comparative Example 2 is that: No magnesium fluoride is added in Comparative Example 2, and magnesium aluminum silicon nitride cannot be formed, which affects the performance of the final alumina ceramic, resulting in poor thermal conductivity and mechanical properties.

[0187] The difference between Example 5 and Comparative Example 3 is that in Comparative Example 4, the alumina is not modified, and there is no in-situ nitrogen source and carbon source during the sintering process, resulting in poor performance of the final alumina ceramic.

[0188] The difference between Example 5 and Comparative Example 4 is that in Comparative Example 5, no phenolic resin and nitrogen source are added to the modified alumina for modification, and there is no in-situ nitrogen source and phenolic resin to form a carbon source during the sintering process, resulting in poor performance of the final alumina ceramic.

[0189] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A silicon nitride ceramic, characterized in that: The preparation comprises the following raw materials in parts by weight: 100 parts of silicon nitride powder, 10 to 20 parts of modified alumina, 5 to 10 parts of aluminum nitride, 10 to 20 parts of magnesium fluoride, 5 to 10 parts of sintering aid and 5 to 10 parts of toughening agent; The modified alumina comprises the following preparation raw materials: 100 parts of aluminum oxide, 30 to 40 parts of alkali, 2 to 3 parts of coupling agent, 1 to 2 parts of polyethylene glycol, 40 to 50 parts of phenolic resin and 200 to 300 parts of nitrogen source; The phenolic resin comprises the following preparation raw materials: 100 parts of phenolic compound, 100 parts to 150 parts of formaldehyde, 2 parts to 3 parts of amine catalyst, 6 parts to 20 parts of boric acid, 50 parts to 60 parts of melamine, and 0 parts to 15 parts of solvent; The phenolic compound includes phenol or 3-hydroxyphenylboronic acid.

2. The silicon nitride ceramic according to claim 1, characterized in that: The amine catalyst is ethylenediamine; And / or, the solvent is at least one of water, ethanol, methanol, acetone, tetrahydrofuran, methane and chloroform.

3. The silicon nitride ceramic according to claim 1, characterized in that: The particle size of the aluminum oxide is 10nm~1000nm; And / or, the coupling agent is γ-piperazinepropylmethyldimethoxysilane; And / or, the Mw of the polyethylene glycol is 800-2000; And / or, the base is aqueous ammonia; And / or, the nitrogen source is melamine.

4. The silicon nitride ceramic according to claim 1, characterized in that: The sintering aid is yttrium oxide; And / or, the toughening agent is silicon carbide.

5. The silicon nitride ceramic according to claim 4, characterized in that: The particle size of the silicon nitride powder is 1 μm to 3 μm; And / or, the yttrium oxide particle size is 1 μm to 10 μm.

6. A method for preparing a silicon nitride ceramic according to any one of claims 1 to 5, characterized in that: The following steps are involved: The modified alumina, aluminum nitride, magnesium fluoride, silicon nitride powder, a sintering aid and a toughening agent are mixed and pressed to obtain a pressed product; The pressed product is nitrided and sintered to obtain silicon nitride ceramics; The atmosphere of the nitriding sintering is nitrogen; The temperature of the nitriding sintering is 700°C to 1700°C.

7. The preparation method according to claim 6, characterized in that: The pressing pressure is 5MPa~10MPa; And / or, the pressing time is 5 min to 10 min.

8. The preparation method according to claim 6, characterized in that: The nitriding sintering includes a first stage nitriding, a second stage nitriding and a third stage nitriding; And / or, the temperature of the first stage nitriding is 700° C. to 800° C.; And / or, the pressure of nitrogen during the first nitriding process is 0.8MPa~1MPa; And / or, the nitriding time in the first nitriding process is 1h~6h; And / or, the temperature of the second stage nitriding is 1500° C. to 1700° C.; And / or, the pressure of nitrogen during the second stage nitriding process is 4MPa~6MPa; And / or, the nitriding time in the second nitriding process is 1h~6h; And / or, the temperature of the third stage nitriding is 950° C. to 1000° C.; And / or, the pressure of nitrogen in the third stage nitriding process is 8MPa~10MPa; And / or, the nitriding time in the third nitriding process is 1 h to 6 h.

9. The preparation method according to claim 6, characterized in that: The preparation method of the modified alumina comprises the following steps: Mixing alumina, a base, a coupling agent, polyethylene glycol and ethanol to prepare a first mixture; The nitrogen source, the phenolic resin and the first mixture are mixed and then dried to prepare modified alumina.

10. The preparation method according to claim 9, characterized in that: The drying temperature is 80°C to 90°C.

Citation Information

Patent Citations

  • Silicon nitride ceramic insulating material used for multipole magnesium electrolysis technology

    CN103848631A

  • Method for low-temperature synthesis and preparation of silicon nitride ceramic powder based on surface modification

    CN109437921A